Organic thin film, organic electroluminescence device, display device and illumination device

The introduction of a 4-benzoic acid-carbazole derivative in the hole injection layer addresses the decomposition issues of acidic dopants, reducing driving voltage and improving stability in organic EL devices through vacuum deposition.

JP2025000413APending Publication Date: 2025-01-07NIPPON HOSO KYOKAI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023100254
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing organic EL devices face issues with acidic dopants that decompose easily, impairing device performance and stability due to high acidity, which complicates manufacturing processes and reduces driving stability.

Method used

The use of a 4-benzoic acid-carbazole derivative with a specific structure in the hole injection layer, which can be deposited via vacuum evaporation, reduces driving voltage and enhances stability by minimizing decomposition and dissolution of the ITO anode.

Benefits of technology

The 4-benzoic acid-carbazole derivative improves hole injection performance, reduces driving voltage, and enhances the stability of organic EL devices, allowing for longer lifespan and improved manufacturing feasibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025000413000014
    Figure 2025000413000014
  • Figure 2025000413000015
    Figure 2025000413000015
  • Figure 2025000413000016
    Figure 2025000413000016
Patent Text Reader

Abstract

To provide an organic thin film that enables its production by a vapor deposition process, reduced driving voltage in organic EL devices, and improved driving stability.SOLUTION: An organic thin film contains a 4-benzoic acid-carbazole derivative.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an organic thin film, an organic electroluminescence (hereinafter, electroluminescence (field emission) may be abbreviated as "EL") element, a display device, and a lighting device. [Background technology]

[0002] Organic EL elements are thin, soft, and flexible. Furthermore, displays using organic EL elements are capable of displaying images with higher brightness and higher resolution than the currently mainstream liquid crystal display devices and plasma display devices. Furthermore, displays using organic EL elements have a wider viewing angle than liquid crystal display devices. For this reason, displays using organic EL elements are currently being used more widely as displays for televisions and mobile phones. Furthermore, organic EL elements are expected to be used as lighting devices.

[0003] In the case of displays using organic EL elements, there are two manufacturing processes: the (printing) coating process and the vacuum deposition process. Currently, in order to produce products that operate at a low voltage and have a long life, manufacturers generally use the vacuum deposition process, in which materials are heated under high vacuum to sublimate and form a film on the substrate. In organic EL elements, a method is widely used in which a p-type dopant material is added to improve hole injection performance when holes are injected into the organic layer from an anode such as ITO.

[0004] Common hole injection materials include materials that form charge transfer complexes with host materials due to their deep LUMO (lowest energy of conduction band) levels, such as hexaazatriphenylene hexacarbonitrile (HAT-CN), 2,3,5,6-tetrafluoro-7,7,8,8-tetracyano-quinodimethane, and molybdenum oxide, and materials that have strong acidic dopants such as sulfonic acid added, such as poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS). Among these, the use of acidic dopants makes it possible to lower the hole injection barrier from the anode to the organic film, regardless of the HOMO (highest energy of valence band) level of the host material that can transport holes, and has the advantage of broadening the options for usable hole transport materials.

[0005] However, it has been confirmed that sulfonic acid-containing materials dissolve the ITO anode, which is the lower electrode, due to their high acidity, and the dissolved indium ions migrate to the vicinity of the light-emitting layer, thereby impairing the operating life of the element (Non-Patent Document 1). [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] Sung Jin Jo et al., J. Appl. Phys., 103, 114502 (2008) Summary of the Invention [Problem to be solved by the invention]

[0007] In addition, many acidic materials have the problems of being easily dehydrated and decomposed by heating, which impairs the performance of the material, and being highly hygroscopic and poor in storage. In particular, dopants containing sulfonic acid or trifluoromethanesulfonyl (Tf) groups, which have high electron-withdrawing properties, are easily decomposed and eliminated by heat, making it difficult to apply the deposition process. For this reason, there have been no reports of acidic dopant materials that can be stably stored and deposited, have low driving voltages, and can improve driving stability.

[0008] Therefore, an object of the present invention is to solve the above-mentioned problems of the conventional technology, and to provide an organic thin film that can be produced by a vapor deposition process, can reduce the driving voltage of an organic EL element, and can improve the driving stability. Another object of the present invention is to provide an organic EL element using such an organic thin film, and a display device and a lighting device including the organic EL element. [Means for solving the problem]

[0009] In order to solve the above problems, the present inventors have conducted various studies on acidic materials that can be used in a hole injection layer located between the anode and light-emitting layer of an organic EL element to improve both the hole injection performance and driving stability of the organic EL element, and that can be formed into a film by a vacuum deposition method. As a result, they have come to the conclusion that a material containing a 4-benzoic acid-carbazole derivative of a specific structure is suitable for manufacturing an organic EL element by a deposition process, and that by using the 4-benzoic acid-carbazole derivative (acidic material) in the hole injection layer of an organic EL element, the driving voltage of the organic EL element to which the deposition process is applied is reduced and the driving stability is improved, thereby solving the above problems, and have arrived at the present invention. That is, the gist and configuration of the organic thin film, organic electroluminescent element, display device, and lighting device of the present invention that solve the above problems are as follows.

[0010] [1] An organic thin film comprising a 4-benzoic acid-carbazole derivative having a structure represented by the following general formula (1): [ka] (In general formula (1), R 1 is selected from functional groups including a thiol group, a carboxyl group, a phospho group, a sulfonyl group, a hydroxyl group, and esters thereof; Ak is a single bond or an alkylene group having 1 to 4 carbon atoms, R 2 , R 3 , R 4 and R 5are each independently selected from hydrogen, a halogen atom, a cyano group, and a fluorinated alkyl group; R 6 are each independently selected from a halogen element, a fluorinated alkyl group, and a fluorinated aryl group. The organic thin film of the present invention described in [1] above can be produced by a vapor deposition process. When applied to an organic EL element, the driving voltage of the organic EL element can be reduced and the driving stability can be improved.

[0011] [2] R in the above general formula (1) 1 is a carboxy group, and R 6 are each independently selected from fluorine, a fluorinated alkyl group, and a fluorinated aryl group. By applying the organic thin film described in the above [2] to an organic EL element, the driving voltage of the organic EL element can be further reduced and the driving stability can be further improved.

[0012] [3] An organic electroluminescence element having a light-emitting layer between a cathode and an anode, An organic electroluminescence element, characterized in that it has a layer containing a first material, which is a 4-benzoic acid-carbazole derivative having a structure represented by the following general formula (1), between the anode and the light-emitting layer. [ka] (In general formula (1), R 1 is selected from functional groups including a thiol group, a carboxyl group, a phospho group, a sulfonyl group, a hydroxyl group, and esters thereof; Ak is a single bond or an alkylene group having 1 to 4 carbon atoms, R 2 , R 3 , R 4 and R 5 are each independently selected from hydrogen, a halogen atom, a cyano group, and a fluorinated alkyl group; R 6are each independently selected from a halogen element, a fluorinated alkyl group, and a fluorinated aryl group. The organic electroluminescence device of the present invention described in [3] above can be produced by a vapor deposition process, and has a low driving voltage and excellent driving stability.

[0013] [4] The organic electroluminescence element according to [3], further comprising a laminated film of a layer containing the first material and a layer containing a second material that transports holes between the anode and the light-emitting layer. The organic electroluminescence element described in [4] above has a lower driving voltage and improved driving stability.

[0014] [5] A layer including the first material and a second material that transports holes is provided between the anode and the light-emitting layer, The organic electroluminescence element according to [3], further comprising a layer containing the second material between the light-emitting layer and the layer containing the first material and the second material. The organic electroluminescence element described in [5] above also has a low driving voltage and improved driving stability.

[0015] [6] A display device comprising the organic electroluminescence element according to any one of [3] to [5]. The display device of the present invention described in [6] above has a low driving voltage and is excellent in driving stability.

[0016] [7] A lighting device comprising the organic electroluminescence element according to any one of [3] to [5]. The lighting device of the present invention described in [7] above has a low driving voltage and is excellent in driving stability. Effect of the Invention

[0017] According to the present invention, it is possible to provide an organic thin film which can be produced by a vapor deposition process, can reduce the driving voltage of an organic EL device, and can improve the driving stability. Furthermore, according to the present invention, it is possible to provide an organic EL element using such an organic thin film, which has a low driving voltage and excellent driving stability, and a display device and a lighting device including the organic EL element. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is a schematic cross-sectional view illustrating an example of an organic EL element of the present invention. [Diagram 2] 19F-NMR spectrum of the 4-benzoic acid-carbazole derivative represented by structural formula (1-1). [Diagram 3] This is a 1H-NMR spectrum of a 4-benzoic acid-carbazole derivative represented by structural formula (1-1). [Figure 4] This is a 19F-NMR spectrum of the 4-benzoic acid-carbazole derivative represented by structural formula (1-2). [Diagram 5] This is a 1H-NMR spectrum of the 4-benzoic acid-carbazole derivative represented by structural formula (1-2). [Figure 6] 1 is a graph showing the relationship between the applied voltage and the luminance of the organic EL elements produced in Examples 1 and 2 and Comparative Examples 1 to 3. [Figure 7] 1 is a graph showing the relationship between the applied voltage and the current density of the organic EL elements produced in Examples 1 and 2 and Comparative Examples 1 to 3. [Figure 8] 1 is a graph showing the change over time in luminance of the organic EL elements produced in Examples 1 to 2 and Comparative Examples 1 to 3, when the initial luminance was set to 10,000 cd / cm2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The organic thin film, the organic electroluminescence element, the display device and the lighting device of the present invention will be illustrated in detail below based on their embodiments.

[0020] [Organic thin film] The organic thin film of the present embodiment is characterized by containing a 4-benzoic acid-carbazole derivative having a structure represented by the following general formula (1). In one embodiment, the organic thin film is a single film containing a first material that is a 4-benzoic acid-carbazole derivative having a structure represented by the following general formula (1), in another embodiment, a single film containing the first material and a second material that transports holes, and in yet another embodiment, a laminated film of a film containing the first material and a film containing the second material. [ka] (In general formula (1), R 1 is selected from functional groups including a thiol group, a carboxyl group, a phospho group, a sulfonyl group, a hydroxyl group, and esters thereof; Ak is a single bond or an alkylene group having 1 to 4 carbon atoms, R 2 , R 3 , R 4 and R 5 are each independently selected from hydrogen, a halogen atom, a cyano group, and a fluorinated alkyl group; R 6 are each independently selected from a halogen element, a fluorinated alkyl group, and a fluorinated aryl group.

[0021] The 4-benzoic acid-carbazole derivative having the structure represented by the above general formula (1) is difficult to decompose by heating, easily sublimes, and has excellent storage stability, and therefore can be applied to the deposition process. In addition, the 4-benzoic acid-carbazole derivative having the structure represented by the above general formula (1) has a lower acidity than the strongly acidic dopants such as the above-mentioned sulfonic acids, and is less likely to dissolve the anode made of ITO, which is the lower electrode. Therefore, by applying the 4-benzoic acid-carbazole derivative having the structure represented by the above general formula (1) to an organic EL element, the driving stability of the organic EL element can be improved. Furthermore, when the organic thin film of the present embodiment contains a second material that transports holes, the second material transports holes, and therefore, by disposing the organic thin film, for example, between the light-emitting layer and the anode of an organic EL element, the hole injection performance can be improved and the driving voltage of the organic EL element can be reduced. Therefore, the organic thin film of this embodiment can be manufactured by a vapor deposition process, and by applying it to an organic EL element, the driving voltage of the organic EL element can be reduced and the driving stability can be improved.

[0022] In the above general formula (1), R 1 is selected from functional groups including a thiol group (-SH), a carboxyl group (-COOH), a phospho group (-P(=O)(OH)2), a sulfo group (-SO3H), a hydroxyl group (-OH), and esters thereof. 1 is selected from functional groups including a thiol group, a carboxyl group, a phospho group, a sulfonyl group, a hydroxyl group, and esters thereof, whereby R 1 has a molecular structure that can coordinate to the anode. Examples of the functional group containing an ester include a group (-SR) in which hydrogen of a thiol group is substituted with an alkyl group (R), a group (-COOR) in which hydrogen of a carboxyl group is substituted with an alkyl group (R), a group (-OR) in which hydrogen of a hydroxyl group is substituted with an alkyl group (R), a group (-P(=O)(OH)(OR), -P(=O)(OR)2 in which hydrogen of a phospho group is substituted with an alkyl group (R), a group (-SO3R) in which hydrogen of a sulfo group is substituted with an alkyl group (R), etc. Here, the number of carbon atoms of the alkyl group (R) is, for example, in the range of 1 to 10, and preferably in the range of 1 to 4.

[0023] In the above general formula (1), Ak is a single bond or an alkylene group having 1 to 4 carbon atoms. Examples of the alkylene group include a methylene group and an ethylene group. Ak is preferably a single bond.

[0024] In the above general formula (1), R 2 , R 3 , R 4 and R 5 are each independently selected from hydrogen, a halogen element, a cyano group, and a fluorinated alkyl group, where the halogen element, the cyano group, and the fluorinated alkyl group are electron-withdrawing functional groups. Examples of halogen elements include fluorine, chlorine, bromine, and iodine, and among these, fluorine is preferred. Examples of the fluorinated alkyl group include a fluoromethyl group, a difluoromethyl group, a trifluoromethyl group, a fluoroethyl group, a difluoroethyl group, a trifluoroethyl group, a tetrafluoroethyl group, and a pentafluoroethyl group. Of these, a trifluoromethyl group is preferable.

[0025] In the above general formula (1), R 6 are each independently selected from a halogen element, a fluorinated alkyl group, and a fluorinated aryl group. These halogen elements, fluorinated alkyl groups, and fluorinated aryl groups are electron-withdrawing functional groups. Examples of halogen elements include fluorine, chlorine, bromine, and iodine, and among these, fluorine is preferred. Examples of the fluorinated alkyl group include a fluoromethyl group, a difluoromethyl group, a trifluoromethyl group, a fluoroethyl group, a difluoroethyl group, a trifluoroethyl group, a tetrafluoroethyl group, and a pentafluoroethyl group. Of these, a trifluoromethyl group is preferable. Examples of the fluorinated aryl group include a fluorophenyl group, a difluorophenyl group, a trifluorophenyl group, a tetrafluorophenyl group, a pentafluorophenyl group, and a fluoronaphthalene group. In addition, in the fluorinated alkyl group and the fluorinated aryl group, a substituent other than fluorine may be bonded to the alkyl group and the aryl group.

[0026] The 4-benzoic acid-carbazole derivative having the structure represented by the above general formula (1) includes R 1 is a carboxy group, and R 6 are preferably compounds in which R is independently selected from fluorine, a fluorinated alkyl group, and a fluorinated aryl group. 1 is a carboxy group, and R 6However, when an organic thin film containing a compound independently selected from fluorine, a fluorinated alkyl group, and a fluorinated aryl group is applied to an organic EL element, the driving voltage of the organic EL element can be further reduced and the driving stability can be further improved.

[0027] Specific examples of the 4-benzoic acid-carbazole derivative having the structure represented by the above general formula (1) include a compound represented by the following structural formula (1-1) and a compound represented by the following structural formula (1-2). [ka]

[0028] The 4-benzoic acid-carbazole derivative having the structure represented by the above general formula (1) can be obtained by synthesis using a known method. The synthesis method of the 4-benzoic acid-carbazole derivative having the structure represented by the general formula (1) is not particularly limited, but an example is shown below.

[0029] First, a phenol having an electron-withdrawing functional group, such as 4-hydroxybenzotrifluoride or 4-fluorophenol, is used as a starting material and reacted with trifluoromethanesulfonic anhydride to convert the hydroxy group into trifluoromethylsulfonylated. Next, the trifluoromethylsulfonylated phenol is reacted with an aniline derivative having an electron-withdrawing functional group, such as 4-aminobenzotrifluoride or 4-fluoroaniline, to produce an amine. Next, the amine compound is cyclized using palladium acetate and acetic acid under an oxygen atmosphere to produce a carbazole derivative. Next, the carbazole derivative is reacted with a benzene derivative having a halogen group and a molecular structure capable of coordinating to an anode, such as ethyl 4-iodobenzoate or ethyl pentafluorobenzoate, and then, if desired, the ester is hydrolyzed to obtain a 4-benzoic acid-carbazole derivative having a structure represented by general formula (1).

[0030] The second material may be any material capable of transporting holes, and is preferably an organic material. More preferably, the second material is an organic material having a highest occupied molecular orbital (HOMO) level of 4.0 eV to 7.0 eV, and particularly preferably a p-type organic semiconductor material having a HOMO level of 4.5 eV to 6.0 eV. For example, any of the conventionally known materials shown below may be used as the material for the hole transport layer of an organic EL device, and among these, a material that satisfies the above HOMO level requirement is preferred. Also, various p-type polymeric materials and various p-type low molecular materials may be used alone or in combination.

[0031] Examples of the p-type polymeric material (organic polymer) include polyarylamine, fluorene-arylamine copolymer, fluorene-bithiophene copolymer, poly(N-vinylcarbazole), polyvinylpyrene, polyvinylanthracene, polythiophene, polyalkylthiophene, polyhexylthiophene, poly(p-phenylenevinylene), polytinylenevinylene, pyrene formaldehyde resin, ethylcarbazole formaldehyde resin, or derivatives thereof. These polymeric materials can also be used as mixtures with other compounds. As an example, a mixture containing polythiophene includes poly(3,4-ethylenedioxythiophene / styrenesulfonic acid) (PEDOT / PSS).

[0032] Examples of the p-type low molecular weight material include arylcycloalkane compounds such as 1,1-bis(4-di-para-triaminophenyl)cyclohexane and 1,1'-bis(4-di-para-tolylaminophenyl)-4-phenyl-cyclohexane, 4,4',4"-trimethyltriphenylamine, N,N,N',N'-tetraphenyl-1,1'-biphenyl-4,4'-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD1), and N,N'-diphenyl- N,N'-bis(4-methoxyphenyl)-1,1'-biphenyl-4,4'-diamine (TPD2), N,N,N',N'-tetrakis(4-methoxyphenyl)-1,1'-biphenyl-4,4'-diamine (TPD3), N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4,4'-diamine (α-NPD), 4,4'-bis[N-phenyl-N-[4'-diphenylamino-1,1'-biphenyl-4-yl]amino]-1,1'-biphenyl (TPTE), tris(4-carbazolyl) arylamine compounds such as N,N,N',N'-tetraphenyl-para-phenylenediamine, N,N,N',N'-tetra(para-tolyl)-para-phenylenediamine, N,N,N',N'-tetra(meta-tolyl)-meta-phenylenediamine (PDA), carbazole compounds such as carbazole, N-isopropylcarbazole, and N-phenylcarbazole, stilbene compounds such as stilbene and 4-di-para-tolylaminostilbene , oxazole-based compounds such as OxZ, triphenylmethane-based compounds such as triphenylmethane, 4,4',4"-tris(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA), pyrazoline-based compounds such as 1-phenyl-3-(para-dimethylaminophenyl)pyrazoline, benzine (cyclohexadiene)-based compounds, triazole-based compounds such as triazole, imidazole-based compounds such as imidazole, 1,3,4-oxadiazole, 2,5-di(4-dimethylaminophenyl)-1,3,Oxadiazole compounds such as 4-oxadiazole, anthracene compounds such as anthracene and 9-(4-diethylaminostyryl)anthracene, fluorenone compounds such as fluorenone, 2,4,7-trinitro-9-fluorenone, and 2,7-bis(2-hydroxy-3-(2-chlorophenylcarbamoyl)-1-naphthylazo)fluorenone, aniline compounds such as polyaniline, silane compounds, pyrrole compounds such as 1,4-dithioketo-3,6-diphenyl-pyrrolo-(3,4-c)pyrrolopyrrole, fluorene compounds such as fluorene, porphyrin, and metal tetraphenyl Examples of the compound include porphyrin-based compounds such as porphyrin, quinacridone-based compounds such as quinacridone, metal or non-metal phthalocyanine-based compounds such as phthalocyanine, copper phthalocyanine, tetra(t-butyl)copper phthalocyanine, and iron phthalocyanine, metal or non-metal naphthalocyanine-based compounds such as copper naphthalocyanine, vanadyl naphthalocyanine, and monochlorogallium naphthalocyanine, and benzidine-based compounds such as N,N'-di(naphthalene-1-yl)-N,N'-diphenyl-benzidine and N,N,N',N'-tetraphenylbenzidine, and the like. One or more of these compounds may be used. Among these, arylamine-based compounds such as TPTE and TCTA are particularly preferred.

[0033] The organic thin film of this embodiment may be a single film containing a 4-benzoic acid-carbazole derivative having a structure represented by general formula (1), or may be a mixed film of a film containing the first material and a film containing a second material that transports holes. Whether it is a single film or a mixed film, it can be manufactured by a deposition process, and by applying it to an organic EL element, the driving voltage of the organic EL element can be reduced and the driving stability can be improved.

[0034] In the case of the mixed film of the present embodiment, the ratio of the first material and the second material contained in the organic thin film is not particularly limited and can be appropriately determined according to the type of compound used for each of the first material and the second material. The ratio of the first material and the second material is preferably 0.1:99.9 to 1:1 in mass ratio (first material:second material), more preferably 0.5:99.5 to 1:2, and even more preferably 1:99 to 1:3. When the ratio is as above, the effect of improving the hole transport property and the hole injection property due to the inclusion of the first material and the second material in the organic thin film becomes significant.

[0035] The organic thin film is preferably formed by a vacuum deposition method such as resistance heating. When the organic thin film is produced by a vapor deposition process, it can be produced by the same method as when other layers constituting an organic EL element are produced by a vapor deposition process. In addition to the production method of forming a film from a 4-benzoic acid-carbazole derivative having the structure represented by the above general formula (1) alone, a production method of an organic thin film including a step of simultaneously vapor-depositing a first material, which is a 4-benzoic acid-carbazole derivative having the structure represented by the above general formula (1), and a second material that transports holes, on the surface on which the organic thin film is to be formed is also one of the preferred embodiments of the production method of an organic thin film of the present invention.

[0036] [Organic EL element] The organic electroluminescence element of this embodiment is characterized in that it has an emitting layer between a cathode and an anode, and has a layer containing a first material, which is a 4-benzoic acid-carbazole derivative having a structure represented by the above general formula (1), between the anode and the emitting layer.

[0037] The organic EL element of the present embodiment uses the 4-benzoic acid-carbazole derivative having the structure represented by the above general formula (1), which is not easily decomposed by heating, has excellent storage stability, and has a relatively low acidity. Therefore, the organic EL element can be manufactured by a vapor deposition process, and has a low driving voltage and excellent driving stability.

[0038] The organic EL device of the present embodiment preferably has a laminated film of a layer containing the first material and a layer containing a second material that transports holes between the anode and the light-emitting layer, which further reduces the driving voltage and improves driving stability. Here, either the layer containing the first material or the layer containing the second material may be disposed on the anode side, but it is preferable that the layer containing the first material is disposed on the anode side, that is, it is preferable to have a layer containing the second material between the light-emitting layer and the layer containing the first material.

[0039] In addition, the organic EL element of the present embodiment preferably has a layer containing the first material and a second material that transports holes between the anode and the light-emitting layer, and a layer containing the second material between the light-emitting layer and the layer containing the first material and the second material. In this case, too, the driving voltage is reduced and driving stability is improved. In the layer containing the first material and the second material, the ratio of the first material to the second material is not particularly limited and can be appropriately determined depending on the type of compound used for each of the first material and the second material. The ratio of the first material to the second material is preferably 0.1:99.9 to 1:1 in mass ratio (first material:second material), more preferably 0.5:99.5 to 1:2, and even more preferably 1:99 to 1:3. When the ratio is as above, the effect of improving hole transportability and hole injection property due to the inclusion of the first material and the second material in the organic thin film becomes significant.

[0040] The first material, which is a 4-benzoic acid-carbazole derivative having a structure represented by the above general formula (1), and the second material that transports holes are as described above in the section "Organic thin film."

[0041] Next, the organic EL device of the present invention will be described in detail with reference to examples. Fig. 1 is a schematic cross-sectional view for explaining one example of an organic EL element of the present invention. The organic EL element 1 of this embodiment shown in Fig. 1 has an emitting layer 6 between an anode 3 and a cathode 9. The organic EL element 1 shown in Fig. 1 has a hole injection layer 4 containing the organic thin film of the present invention, i.e., a 4-benzoic acid-carbazole derivative having a structure represented by the above general formula (1), between the anode 3 and the emitting layer 6. The organic EL element 1 of this embodiment has a laminated structure in which an anode 3, a hole injection layer 4, a hole transport layer 5, a light-emitting layer 6, an electron transport layer 7, an electron injection layer 8, and a cathode 9 are formed in this order on a substrate 2.

[0042] The organic EL element 1 shown in FIG. 1 may be of a top emission type in which light is extracted from the side opposite to the substrate 2, or of a bottom emission type in which light is extracted from the substrate 2 side.

[0043] (substrate) Examples of the material for the substrate 2 include a resin material, a glass material, etc. The material for the substrate 2 may be one type alone or a combination of two or more types. Examples of the resin material used for the substrate 2 include polyethylene terephthalate, polyethylene naphthalate, cycloolefin polymer, polyamide, polyethersulfone, polymethyl methacrylate, polycarbonate, polyarylate, etc. When a resin material is used as the material for the substrate 2, it is preferable because an organic EL element 1 having excellent flexibility can be obtained. On the other hand, examples of the glass material used for the substrate 2 include quartz glass and soda glass.

[0044] When the organic EL element 1 is of a bottom emission type, the material of the substrate 2 is a transparent substrate. On the other hand, when the organic EL element 1 is of a top emission type, not only a transparent substrate but also an opaque substrate may be used as the material of the substrate 2. Examples of opaque substrates include a substrate made of a ceramic material such as alumina, a substrate in which an oxide film (insulating film) is formed on the surface of a metal plate such as stainless steel, and a substrate made of a resin material.

[0045] The average thickness of the substrate 2 can be determined depending on the material of the substrate 2, and is preferably 0.1 to 30 mm, and more preferably 0.1 to 10 mm. The average thickness of the substrate 2 can be measured with a digital multimeter and a vernier caliper.

[0046] (electrode) In the organic EL device 1 of this embodiment, the anode 3 and the cathode 9 may be made of known conductive materials, but it is preferable that at least one of them is transparent in order to extract light. Examples of known transparent conductive materials include ITO (tin-doped indium oxide), ATO (antimony-doped indium oxide), IZO (indium-doped zinc oxide), AZO (aluminum-doped zinc oxide), and FTO (fluorine-doped indium oxide). A heterogeneous metal and metal oxide ultrathin film having a thickness of about 0.1 to 3 nm may be laminated on these transparent conductive materials. On the other hand, examples of opaque conductive materials include calcium, magnesium, aluminum, barium, tin, indium, copper, silver, ytterbium, and alloys thereof. Of these, ITO, IZO, and FTO are preferable for the anode 3. On the other hand, among these, Al, AgMg, and AgYb alloys are preferable for the cathode 9.

[0047] The average thickness of the anode 3 is not particularly limited, but is preferably 10 to 500 nm, and more preferably 70 to 200 nm. The average thickness of the anode 3 can be measured by a stylus step gauge or spectroscopic ellipsometry.

[0048] The average thickness of the cathode 9 is not particularly limited, but is preferably 10 to 1000 nm, and more preferably 30 to 150 nm. Even when an opaque material is used, the cathode 9 can be used as a top emission type or transparent type cathode 9 by setting the average thickness to, for example, about 10 to 30 nm. The average thickness of the cathode 9 can be measured during film formation using a quartz crystal film thickness meter.

[0049] (Hole injection layer) The hole injection layer 4 can have the same structure as the organic thin film described above, and this structure makes it possible to form a hole injection layer 4 with improved hole injection properties and stability. Also, a part of the organic thin film described above may be the hole injection layer 4, and another part of the organic thin film may be the hole transport layer 5 described later. For example, a mixed film of the first material and the second material may be the hole injection layer 4, and a film made of the second material may be the hole transport layer 5, a film made only of the first material may be the hole injection layer 4, and a film made only of the second material may be the hole transport layer 5, a laminated film of the second material and the first material may be the hole injection layer 4, and a film made only of the second material may be the hole transport layer 5, or a mixed film of the first material and the second material may be the hole injection layer 4 and hole transport layer 5. In addition, when the hole injection layer 4 contains a first material (dopant) and a second material (host material), the mass ratio of the first material to the second material (first material:second material) is preferably 0.1:99.9 to 1:1, and more preferably 1:99 to 1:2.

[0050] The average thickness of the hole injection layer 4 is not particularly limited, but is preferably 1 to 1000 nm, and more preferably 1 to 50 nm. The average thickness of the hole injection layer 4 can be measured by, for example, a stylus step gauge or spectroscopic ellipsometry.

[0051] (Hole transport layer) Any compound that can be generally used as a material for a hole transport layer can be used as the material for the hole transport layer 5, and various p-type polymeric materials and various p-type low molecular weight materials can be used alone or in combination. For example, the various materials exemplified as the second material for the organic thin film described above can be used.

[0052] Examples of the p-type polymeric material (organic polymer) include polyarylamine, fluorene-arylamine copolymer, fluorene-bithiophene copolymer, poly(N-vinylcarbazole), polyvinylpyrene, polyvinylanthracene, polythiophene, polyalkylthiophene, polyhexylthiophene, poly(p-phenylenevinylene), polytinylenevinylene, pyrene formaldehyde resin, ethylcarbazole formaldehyde resin, or derivatives thereof. These polymeric materials can also be used as mixtures with other compounds. As an example, a mixture containing polythiophene includes poly(3,4-ethylenedioxythiophene / styrenesulfonic acid) (PEDOT / PSS).

[0053] Examples of the p-type low molecular weight material include arylcycloalkane compounds such as 1,1-bis(4-di-para-triaminophenyl)cyclohexane and 1,1'-bis(4-di-para-tolylaminophenyl)-4-phenyl-cyclohexane, 4,4',4"-trimethyltriphenylamine, N,N,N',N'-tetraphenyl-1,1'-biphenyl-4,4'-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD1), and N,N'-diphenyl- N,N'-bis(4-methoxyphenyl)-1,1'-biphenyl-4,4'-diamine (TPD2), N,N,N',N'-tetrakis(4-methoxyphenyl)-1,1'-biphenyl-4,4'-diamine (TPD3), N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4,4'-diamine (α-NPD), 4,4'-bis[N-phenyl-N-[4'-diphenylamino-1,1'-biphenyl-4-yl]amino]-1,1'-biphenyl (TPTE), tris(4-carbazolyl) arylamine compounds such as N,N,N',N'-tetraphenyl-para-phenylenediamine, N,N,N',N'-tetra(para-tolyl)-para-phenylenediamine, N,N,N',N'-tetra(meta-tolyl)-meta-phenylenediamine (PDA), carbazole compounds such as carbazole, N-isopropylcarbazole, and N-phenylcarbazole, stilbene compounds such as stilbene and 4-di-para-tolylaminostilbene , oxazole-based compounds such as OxZ, triphenylmethane-based compounds such as triphenylmethane, 4,4',4"-tris(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA), pyrazoline-based compounds such as 1-phenyl-3-(para-dimethylaminophenyl)pyrazoline, benzine (cyclohexadiene)-based compounds, triazole-based compounds such as triazole, imidazole-based compounds such as imidazole, 1,3,4-oxadiazole, 2,5-di(4-dimethylaminophenyl)-1,3,Oxadiazole compounds such as 4-oxadiazole, anthracene compounds such as anthracene and 9-(4-diethylaminostyryl)anthracene, fluorenone compounds such as fluorenone, 2,4,7-trinitro-9-fluorenone, and 2,7-bis(2-hydroxy-3-(2-chlorophenylcarbamoyl)-1-naphthylazo)fluorenone, aniline compounds such as polyaniline, silane compounds, pyrrole compounds such as 1,4-dithioketo-3,6-diphenyl-pyrrolo-(3,4-c)pyrrolopyrrole, fluorene compounds such as fluorene, porphyrin, and metal tetraphenyl Examples of the compound include porphyrin-based compounds such as porphyrin, quinacridone-based compounds such as quinacridone, metal or non-metal phthalocyanine-based compounds such as phthalocyanine, copper phthalocyanine, tetra(t-butyl)copper phthalocyanine, and iron phthalocyanine, metal or non-metal naphthalocyanine-based compounds such as copper naphthalocyanine, vanadyl naphthalocyanine, and monochlorogallium naphthalocyanine, and benzidine-based compounds such as N,N'-di(naphthalene-1-yl)-N,N'-diphenyl-benzidine and N,N,N',N'-tetraphenylbenzidine, and the like. One or more of these compounds may be used. Among these, arylamine-based compounds such as TPTE and TCTA are particularly preferred.

[0054] The average thickness of the hole transport layer 5 is not particularly limited, but is preferably from 10 to 150 nm, and more preferably from 20 to 100 nm. The average thickness of the hole transport layer 5 can be measured by, for example, a stylus step gauge or spectroscopic ellipsometry.

[0055] (Light Emitting Layer) In the organic EL element 1 of the present embodiment, the material forming the light-emitting layer 6 may be a low molecular weight compound or a high molecular weight compound, or a mixture of these may be used. In the present invention, the low molecular weight material means a material that is not a high molecular weight material (polymer), and does not necessarily mean an organic compound with a low molecular weight.

[0056] Examples of polymeric materials for forming the light-emitting layer 6 include polyacetylene-based compounds such as trans-polyacetylene, cis-polyacetylene, poly(diphenylacetylene) (PDPA), and poly(alkyl, phenylacetylene) (PAPA); poly(para-phenylenevinylene) (PPV), poly(2,5-dialkoxy-para-phenylenevinylene) (RO-PPV), cyano-substituted-poly(para-phenylenevinylene) (CN-PPV), poly( Polyparaphenylenevinylene compounds such as 2-dimethyloctylsilyl-paraphenylenevinylene) (DMOS-PPV) and poly(2-methoxy,5-(2'-ethylhexoxy)-paraphenylenevinylene) (MEH-PPV); polythiophene compounds such as poly(3-alkylthiophene) (PAT) and poly(oxypropylene)triol (POPT); poly(9,9-dialkylfluorene) (PDAF) and poly(dioctylfluorene) Polyfluorene compounds such as α,ω-bis[N,N'-di(methylphenyl)aminophenyl]-poly[9,9-bis(2-ethylhexyl)fluorene-2,7-dyl] (PF2 / 6am4), poly(9,9-dioctyl-2,7-divinylenefluorenyl-ortho-co(anthracene-9,10-diyl); poly(para-phenylene) (PPP), poly(1,5-dialkoxy- ... Examples of suitable polymeric materials include polyparaphenylene-based compounds such as poly(paraphenylene) (RO-PPP) and the like; polycarbazole-based compounds such as poly(N-vinylcarbazole) (PVK) and the like; polysilane-based compounds such as poly(methylphenylsilane) (PMPS), poly(naphthylphenylsilane) (PNPS) and poly(biphenylylphenylsilane) (PBPS) and the like; and further examples of suitable polymeric materials include boron compound-based polymeric materials described in JP-A-2011-184430 and JP-A-2012-151148.

[0057] Examples of low molecular weight materials for forming the light emitting layer 6 include three-coordinate iridium complexes, such as fac-tris(3-methyl-2-phenylpyridinato-N,C2'-)iridium(III) (Ir(mppy)3), fac-tris(2-phenylpyridine)iridium (Ir(ppy)3), 8-hydroxyquinoline aluminum (Alq3), tris(4-methyl-8-quinolinolato)aluminum(III) (Almq3), 8-hydroxyquinoline zinc (Znq2), (1,10-phenanthroline)-tris-(4,4 ,4-trifluoro-1-(2-thienyl)-butane-1,3-dionate) europium(III) (Eu(TTA)3(phen)), 2,3,7,8,12,13,17,18-octaethyl-21H,23H-porphine platinum(II), and other metal complexes; benzene-based compounds such as distyrylbenzene (DSB) and diaminodistyrylbenzene (DADSB), naphthalene-based compounds such as naphthalene and Nile Red, phenanthrene-based compounds such as phenanthrene, and chrysene-based compounds such as chrysene and 6-nitrochrysene. compounds, perylene, perylene-based compounds such as N,N'-bis(2,5-di-t-butylphenyl)-3,4,9,10-perylene-di-carboximide (BPPC), coronene-based compounds such as coronene, anthracene-based compounds such as anthracene and bisstyrylanthracene, pyrene-based compounds such as pyrene, pyran-based compounds such as 4-(di-cyanomethylene)-2-methyl-6-(para-dimethylaminostyryl)-4H-pyran (DCM), acridine-based compounds such as acridine, stilbene-based compounds such as stilbene, 4,4' -Carbazole compounds such as bis[9-dicarbazolyl]-2,2'-biphenyl (CBP) and 4,4'-bis(9-ethyl-3-carbazovinylene)-1,1'-biphenyl (BCzVBi), thiophene compounds such as 2,5-dibenzoxazolethiophene, benzoxazole compounds such as benzoxazole, benzimidazole compounds such as benzimidazole, benzothiazole compounds such as 2,2'-(para-phenylenedivinylene)-bisbenzothiazole, bistyryl(1,4-diphenyl-1,3-butadiene), butadiene compounds such as tetraphenylbutadiene, naphthalimide compounds such as naphthalimide, coumarin compounds such as coumarin, perinone compounds such as perinone, oxadiazole compounds such as oxadiazole, aldazine compounds, cyclopentadiene compounds such as 1,2,3,4,5-pentaphenyl-1,3-cyclopentadiene (PPCP), quinacridone compounds such as quinacridone and quinacridone red, pyridine compounds such as pyrrolopyridine and thiadiazolopyridine, 2,4-diphenylpyridine, Examples of the material include triazine compounds such as phenyl-6-bis(12-phenylindolo)[2,3-a]carbazol-11-yl)-1,3,5-triazine (DIC-TRZ), spiro compounds such as 2,2',7,7'-tetraphenyl-9,9'-spirobifluorene, metal or non-metal phthalocyanine compounds such as phthalocyanine (HPc) and copper phthalocyanine, and boron compound materials described in JP-A-2009-155325 and JP-A-5660371. One or more of these materials can be used. Quantum dots and perovskite materials can also be used as the light-emitting layer.

[0058] The average thickness of the light-emitting layer 6 is not particularly limited, but is preferably from 10 to 150 nm, and more preferably from 20 to 100 nm. The average thickness of the light-emitting layer 6 may be measured by a stylus-type step gauge, or may be measured by a quartz crystal thickness gauge during the deposition of the light-emitting layer 6.

[0059] (electron transport layer) As the material for the electron transport layer 7, a wide variety of known materials capable of transporting electrons can be used. Specifically, phosphine oxide derivatives such as phenyl-dipyrenylphosphine oxide (POPy2), pyridine derivatives such as tris-1,3,5-(3'-(pyridin-3"-yl)phenyl)benzene (TmPhPyB), quinoline derivatives such as (2-(3-(9-carbazolyl)phenyl)quinoline (mCQ)), 2-phenyl-4,6-bis(3,5-dipyridylphenyl)pyrimidine (BPyPPM), 4,6-bis(3,5-di pyrimidine derivatives such as (pyridin-3-yl)phenyl)-2-methylpyrimidine (B3PyMPM), pyrazine derivatives, phenanthroline derivatives such as bathophenanthroline (BPhen), triazine derivatives such as 2,4-bis(4-biphenyl)-6-(4'-(2-pyridinyl)-4-biphenyl)-[1,3,5]triazine (MPT) and 2,4,6-tris(m-pyridin-3-yl-phenyl)triazine (TmPPyTz), 3-phenyl-4-(1'-naphthyl)-5-phenyl-1,2,4-triazole (T AZ), triazole derivatives, oxazole derivatives, oxadiazole derivatives, such as 2-(4-biphenylyl)-5-(4-tert-butylphenyl-1,3,4-oxadiazole) (PBD), imidazole derivatives, such as 2,2',2"-(1,3,5-benzotriyl)-tris(1-phenyl-1-H-benzimidazole) (TPBI), aromatic ring tetracarboxylic acid anhydrides, such as naphthalene and perylene, bis[2-(2-hydroxyphenyl)benzothiazolato]zinc (Zn(BTZ)2), tris(8-hydroxyquinolinyl) Examples of the metal complexes include various metal complexes represented by (6'-(2',2"-bipyridyl-1,1-dimethyl-3,4-diphenylsilole (Alq3) and the like; organic silane derivatives represented by silole derivatives such as 2,5-bis(6'-(2',2"-bipyridyl-1,1-dimethyl-3,4-diphenylsilole (PyPySPyPy) and the like; and boron-containing compounds described in JP 2013-239691 A, WO 2014 / 133141 A, JP 2016-172728 A, JP 2016-199507 A, and JP 2016-199508 A. One or more of these can be used.

[0060] The average thickness of the electron transport layer 7 is not particularly limited, but is preferably 10 to 150 nm, and more preferably 20 to 100 nm. The average thickness of the electron transport layer 7 can be measured by a stylus step gauge or spectroscopic ellipsometry.

[0061] (electron injection layer) The material used for the electron injection layer 8 is selected from the viewpoints of the work function of the cathode 9 and the LUMO level of the electron transport layer 7. When the electron transport layer 7 is not provided, the material is selected in consideration of the LUMO level of the material used for the light emitting layer 6. The material for the electron injection layer 8 may be an organic compound or an inorganic compound. When the electron injection layer 8 is made of an inorganic compound, for example, lithium fluoride, sodium fluoride, potassium fluoride, cesium fluoride, cesium carbonate, etc., in addition to alkali metals and alkaline earth metals, can be used. When the electron injection layer 8 is made of an organic compound, for example, 8-quinolinolatolithium (Liq) can be used.

[0062] The average thickness of the electron injection layer 8 can be from 1 nm to several μm, but is preferably 1 to 1000 nm, and more preferably 2 to 100 nm, from the viewpoint of obtaining an organic EL element that can be driven at a low voltage. The average thickness of the electron injection layer 8 can be measured by a stylus step gauge or spectroscopic ellipsometry.

[0063] (Formation method) The organic EL device 1 shown in FIG. 1 can be manufactured by forming an anode 3, a hole injection layer 4, a hole transport layer 5, a light emitting layer 6, an electron transport layer 7, an electron injection layer 8, and a cathode 9 in this order on a substrate 2. The method of forming each layer of the anode 3, the hole injection layer 4, the hole transport layer 5, the light emitting layer 6, the electron transport layer 7, the electron injection layer 8, and the cathode 9 is not particularly limited, and each layer can be formed by appropriately using various conventionally known formation methods according to the characteristics of the material used for each layer. Methods of forming each layer include chemical vapor deposition (CVD) such as plasma CVD, thermal CVD, and laser CVD, which are gas phase film formation methods, dry plating methods such as vacuum deposition, sputtering, and ion plating, and spraying methods, and wet plating methods such as electrolytic plating, immersion plating, and electroless plating, which are liquid phase film formation methods, and printing techniques such as the sol-gel method, MOD method, spray pyrolysis method, doctor blade method using a fine particle dispersion, spin coating method, inkjet method, and screen printing method. It is preferable to select these methods depending on the characteristics of the material of each layer, and the manufacturing method may differ for each layer.

[0064] The organic EL element 1 of the present embodiment can change the emission color by appropriately selecting the material of the light-emitting layer 6, and can also obtain a desired emission color by using a color filter or the like in combination. Therefore, the organic EL element of the present invention can be suitably used in display devices and lighting devices.

[0065] (Other examples) The organic EL element of the present invention is not limited to the organic EL element described in the above-mentioned embodiment. Specifically, in the above-described embodiment, the organic EL element 1 having a forward structure in which the anode 3 is disposed between the substrate 2 and the light-emitting layer 6 has been described as an example, but the organic EL element of the present invention may have an inverted structure in which the cathode is disposed between the substrate and the light-emitting layer.

[0066] In the organic EL device of the present invention, the hole transport layer, the electron transport layer and the electron injection layer may be formed as necessary, and may not be provided. Further, each layer of the anode, hole injection layer, hole transport layer, light-emitting layer, electron transport layer, electron injection layer, and cathode may be formed of a single layer or may be composed of two or more layers. In addition, the organic EL element of the present invention may have other layers between each layer of the anode, hole injection layer, hole transport layer, light-emitting layer, electron transport layer, electron injection layer, and cathode. Specifically, for reasons such as further improving the characteristics of the organic EL element, an electron blocking layer or the like may be provided as necessary.

[0067] [Display device] The display device of the present invention is characterized by including the above-described organic electroluminescence element. Since the display device of the present invention includes an organic EL element having a low driving voltage and excellent driving stability as described above, it has a low driving voltage and excellent driving stability. In addition to the above-described organic electroluminescence element, the display device of the present invention can include other components generally used in display devices.

[0068] [Lighting device] The lighting device of the present invention is characterized by including the above-described organic electroluminescence element. Since the lighting device of the present invention includes an organic EL element having a low driving voltage and excellent driving stability as described above, it has a low driving voltage and excellent driving stability. In addition to the above-described organic electroluminescence element, the lighting device of the present invention can include other components generally used in lighting devices.

Examples

[0069] Hereinafter, the present invention will be described in more detail with reference to examples, but the present invention is not limited to the following examples at all.

[0070] <NMR measurement method> JEOL's AL400 was used. The spectrometer is an AL-Series spectrometer, and the probe is a TH5ATFG2 probe.

[0071] <Synthesis method of the compound represented by structural formula (1-1)> The compound represented by structural formula (1-1) was synthesized according to the following reaction scheme. [ka]

[0072] "Synthesis process of the compound represented by formula (2-2)" In an argon atmosphere, 4-hydroxybenzotrifluoride (25g, 0.154mol, 1.0eq.) represented by formula (2-1), anhydrous pyridine (18.7mL, 0.231mol, 1.5eq.), and anhydrous dichloromethane (250mL) were added to a 1L reactor. Trifluoromethanesulfonic anhydride (27.8mL, 0.170mol, 1.1eq.) was slowly added dropwise to this solution over 5 minutes at 5°C under ice cooling. After stirring this suspension at the same temperature for 15 minutes, the cooling bath was removed and the suspension was stirred at room temperature for 3 hours. After deoxygenation under reduced pressure, t-Bu3P (0.5M toluene solution) (0.6mL, 0.304mmol, 0.05eq.) was added and the suspension was heated and stirred at a bath temperature of 80°C for 6 hours. A 0.5N aqueous hydrochloric acid solution (200mL) was added to this suspension and separated into two layers. The aqueous layer was extracted with chloroform (150 mL), and the combined organic layers were washed with saturated sodium bicarbonate water, tap water, and saturated saline, successively, and dried over anhydrous sodium sulfate. The filtrate was concentrated to obtain a light reddish brown liquid of the compound represented by formula (2-2) (45.4 g, 0.154 mol, quantitative), which was used as it was in the next reaction.

[0073] "Synthesis process of the compound represented by formula (2-3)" In an argon atmosphere, a compound represented by formula (2-2) (45.4 g, 0.154 mmol, 1.0 eq.), 4-aminobenzotrifluoride (32.5 g, 0.202 mol, 1.3 eq.), X-Phos (7.34 g, 15.4 mmol, 0.1 eq.), cesium carbonate (60.2 g, 0.185 mol, 1.2 eq.), and degassed toluene (900 mL) were added to a 2 L reactor. The suspension was degassed at room temperature under reduced pressure for 10 minutes, and then palladium acetate (2.08 g, 9.24 mmol, 0.06 eq.) was added. The suspension was heated to a bath temperature of 100°C and heated and stirred for 18 hours. After cooling to room temperature, the suspension was filtered through Celite, and the filtrate was concentrated to obtain a black-yellow viscous liquid (49.5 g, wet). This was purified by a column (SiO2 = 1.2 kg, heptane / ethyl acetate = 7 / 1 → 5 / 1) to obtain a pale red solid compound represented by formula (2-3) (34.0 g, 0.111 mol, 72%).

[0074] "Synthesis process 1 of the compound represented by formula (2-4)" A compound represented by formula (2-3) (20 g, 65.5 mmol, 1.0 eq.), palladium acetate (0.737 g, 3.28 mmol, 0.1 eq.), and acetic acid (200 mL) were added to a 500 mL reactor. The suspension was degassed under reduced pressure while replacing with oxygen, and then vigorously stirred at 90°C for 72 hours under an oxygen atmosphere. The suspension was slowly added dropwise to vigorously stirred saturated sodium bicarbonate water (2.5 L) while being careful not to foam, and after stirring at room temperature for 30 minutes, the suspension was extracted with ethyl acetate (1 L, 0.5 L). The organic layers were combined, washed with city water and saturated saline, dried over anhydrous sodium sulfate, and concentrated to obtain a black-reddish brown solid (23 g). This was purified by column (SiO2 = 250 g, heptane / ethyl acetate = 5 / 1 → 3 / 1 → 1 / 1 → ethyl acetate only) to obtain a light brown viscous liquid (5.4 g). This was washed by heating and dispersion in heptane / chloroform = 10 / 1 (20 mL), allowed to cool, cooled to 5 ° C, filtered, washed with hexane, and dried at 40 ° C under high vacuum to obtain compound 1 (3.9 g, 12.8 mmol, 19%) represented by formula (2-4) as a beige powder.

[0075] "Synthesis process 2 of the compound represented by formula (2-4)" A compound represented by formula (2-3) (13 g, 42.6 mmol, 1.0 eq.), palladium acetate (0.67 g, 2.98 mmol, 0.07 eq.), and acetic acid (130 mL) were added to a 500 mL reactor. The suspension was degassed under reduced pressure while replacing with oxygen, and then vigorously stirred at 90°C for 72 hours under an oxygen atmosphere. The suspension was slowly added dropwise to vigorously stirred saturated sodium bicarbonate water (2 L) while being careful not to foam, and after stirring at room temperature for 30 minutes, the suspension was extracted with ethyl acetate (1.5 L). The organic layers were combined, washed with city water and saturated saline, dried over anhydrous sodium sulfate, and concentrated to obtain a black-reddish brown solid (15 g). This was purified by column (SiO2 = 230 g, heptane / ethyl acetate = 3 / 1 → 1 / 1 → ethyl acetate only) to obtain a light brown viscous liquid (5.9 g). This was washed by heating and dispersion with heptane / chloroform = 10 / 1 (10 mL), allowed to cool, cooled to 5 ° C, filtered, washed with hexane, and dried at 40 ° C under high vacuum to obtain compound 2 (4.2 g, 13.8 mmol, 32%) represented by formula (2-4) as a beige powder.

[0076] "Synthesis process of the compound represented by formula (2-5)" In a 100mL reactor, compound 1 represented by formula (2-4) (1.7g, 5.61mmol, 1.0eq.), ethyl 4-iodobenzoate (2.9g, 11.2mmol, 2.0eq.), copper powder (for Ullmann) (0.712g, 11.2mmol, 2.0eq.), 18-crown-6-ether (0.74g, 2.80mmol, 0.5eq.), potassium carbonate (fine powder dried product) (2.32g, 16.8mmol, 3.0eq.), and 1,2-dichlorobenzene (25mL) were added. The suspension was heated and stirred at a bath temperature of 210°C for 24 hours. After cooling, the suspension was filtered through Celite, the filter bed was washed with toluene (20mL), and the filtrate was concentrated to obtain a brown suspension residue (containing dichlorobenzene). This was purified by column (SiO2=80g, heptane / ethyl acetate=7 / 1→5 / 1) to obtain a brown solid (1.44g). This was purified again by column (SiO2=50g, heptane / toluene=1 / 1→1 / 2→toluene only) to obtain a light brown solid (1.25g). This was dispersed and washed with ethanol and dried at 80°C under high vacuum to obtain a light yellow solid compound represented by formula (2-5) (1.20g, 2.70mmol, 48%).

[0077] "Synthesis process of the compound represented by formula (1-1)" In a 50 mL reactor, the compound represented by formula (2-5) (1.2 g, 2.70 mmol, 1.0 eq.), 2N NaOH aqueous solution (6.6 mL, 13.3 mmol, 5.0 eq.), and THF (24 mL) were added. The mixture was stirred at room temperature for 24 hours. 1N HCl aqueous solution was added to this colorless solution until the pH was about 1, and the solution was extracted with ethyl acetate (10 mL x 2). The organic layers were combined, washed with saturated saline (20 mL x 5), dried over anhydrous magnesium sulfate, and concentrated to obtain a light yellow powder (1.1 g). This was ultrasonically washed with hexane / ethyl acetate = 1 / 1 (20 mL), filtered, and dried at 60 ° C under high vacuum to obtain a colorless solid compound represented by formula (1-1) (0.97 g, 2.29 mmol, 86%). The NMR analysis results of the synthesized compound represented by formula (1-1) are shown in FIG. 2 and FIG.

[0078] <Method for synthesizing the compound represented by structural formula (1-2)> The compound represented by the structural formula (1-2) was synthesized according to the following reaction scheme. [ka]

[0079] "Synthesis process of the compound represented by formula (3-1)" Compound 2 (1.1 g, 3.62 mmol, 1.0 eq.) represented by formula (2-4) and DMF (11 mL) were added to a 50 mL reactor under an argon atmosphere. NaH (60%) (0.145 g, 3.62 mmol, 1.0 eq.) was added to this solution under ice cooling, and the mixture was stirred at the same temperature for 1 hour, and it was confirmed that the bubbling of hydrogen gas had subsided. Ethyl pentafluorobenzoate (1.05 g, 4.35 mmol, 1.2 eq.) was added to this light yellow solution, and the mixture was stirred at the same temperature for 15 minutes, after which the cooling bath was removed and the mixture was stirred at room temperature for 8 hours. This suspension was added to a 10% aqueous ammonium chloride solution (30 mL) and stirred, and then ethyl acetate (30 mL) was added to separate it into two layers. The aqueous layer was extracted with ethyl acetate (20 mL), and the organic layer was combined and washed with tap water and saturated saline in that order, dried over anhydrous sodium sulfate, and concentrated to obtain a dark brown powder (1.99 g). This was purified by column chromatography (SiO2=70 g, heptane / ethyl acetate=7 / 1→5 / 1) to obtain a light red solid (1.66 g). This was dispersed and washed with heated ethanol and dried at 60°C under high vacuum to obtain a colorless solid compound represented by formula (3-1) (1.50 g, 2.87 mmol, 79%).

[0080] "Synthesis process of the compound represented by formula (1-2)" In a 50mL reactor, the compound represented by formula (3-1) (1.5g, 2.87mmol, 1.0eq.), 2N NaOH aqueous solution (15mL, 30mmol, 10.4eq.), and THF (30mL) were added. After stirring this mixture for 24 hours at room temperature, 1N HCl aqueous solution was added to this colorless solution until the pH became about 1, and the solution was extracted with ethyl acetate (15mL x 2). The organic layers were combined and washed with saturated saline (30mL x 5), dried over anhydrous magnesium sulfate, and concentrated to obtain a light yellow powder (1.39g). This was ultrasonically washed with hexane / ethyl acetate = 1 / 1 (20mL), filtered, and dried at 60°C under high vacuum to obtain a colorless solid compound represented by formula (1-2) (0.97g, 2.29mmol, 86%). The NMR analysis results of the synthesized compound represented by formula (1-2) are shown in FIG. 4 and FIG.

[0081] Example 1 <Manufacturing of organic EL elements> An organic EL device 1 having the structure shown in FIG. 1 was produced by the method described below. A commercially available transparent glass substrate with an average thickness of 0.7 mm and a patterned electrode (anode 3) made of ITO with a thickness of 100 nm was prepared as the substrate 2. The substrate 2 having the anode 3 was ultrasonically cleaned in a weak alkaline cleaner, acetone, and isopropanol, and then UV ozone cleaned for 30 minutes. Then, an annealing treatment was performed at 150°C for 30 minutes in the atmosphere. Next, the substrate 2 was fixed to a substrate holder in the chamber of a vacuum deposition device, and the inside of the chamber of the vacuum deposition device was filled with 1.5×10 -5 The pressure was reduced to 100 MPa, and a hole injection layer 4, a hole transport layer 5, a light emitting layer 6, an electron transport layer 7, an electron injection layer 8, and a cathode 9 were successively formed by a vacuum deposition method using resistance heating.

[0082] First, a hole injection layer 4 made of the compound represented by the above structural formula (1-1) was formed to a thickness of 1.5 nm.

[0083] Subsequently, a hole transport layer 5 made of a compound (TCTA) represented by the following structural formula and having a thickness of 35 nm was formed. [ka]

[0084] Next, a compound represented by the following structural formula (DIC-TRZ) was used as a host, and a compound represented by the following structural formula (Ir(mppy)3) was used as a dopant, and co-evaporated to a thickness of 30 nm to form an emitting layer 6. At this time, the doping concentration of Ir(mppy)3 was set to 3 mass % relative to the entire emitting layer 6. [ka]

[0085] Next, on the substrate on which the light-emitting layer 6 had been formed, a compound represented by the following structural formula (B3PyMPM) was formed to a thickness of 40 nm, and then lithium fluoride (LiF) was formed to a thickness of 0.8 nm to form an electron transport layer 7 and an electron injection layer 8, respectively. [ka]

[0086] Next, a cathode 9 made of aluminum and having a thickness of 100 nm was formed on the substrate on which the electron injection layer 8 had been formed. The cathode 9 was formed using a stainless steel deposition mask so that the deposition surface would be in the shape of a strip with a width of 3 mm, and the light-emitting area of ​​the fabricated organic EL element 1 was set to 9 mm 2 It was decided.

[0087] Example 2 An organic EL device 1 of Example 2 was obtained in the same manner as in Example 1, except that the hole injection layer 4 in Example 1 was changed to the compound represented by the above structural formula (1-2).

[0088] Comparative Example 1 An organic EL device 1 of Comparative Example 1 was obtained in the same manner as in Example 1, except that a hole injection layer 4 was formed by depositing a 5 nm film of a compound represented by the following structural formula (hexaazatriphenylene hexacarbonitrile, HAT-CN) on an anode 3 made of ITO. [ka]

[0089] Comparative Example 2 An organic EL device 1 of Comparative Example 2 was obtained in the same manner as in Example 1, except that a film of a compound (F4-TCNQ) represented by the following structural formula was formed to a thickness of 1.5 nm on an anode 3 made of ITO in Example 1 to serve as a hole injection layer 4. [ka]

[0090] Comparative Example 3 An organic EL device 1 of Comparative Example 3 was obtained in the same manner as in Example 1, except that the hole injection layer 4 was not formed on the anode 3 made of ITO.

[0091] <Measurement of the light-emitting properties of organic EL elements> A voltage was applied to the organic EL elements produced in Examples 1 and 2 and Comparative Examples 1 to 3 using a Keithley 2400-type source meter, and the luminance was measured using a Konica Minolta LS-100 to investigate the relationship between the applied voltage and the luminance, the relationship between the applied voltage and the current density, and the change over time in the luminance under a constant current density when the initial luminance was 10,000 nits. The results are shown in Figures 6 to 8.

[0092] <Result> In both Examples 1 and 2, organic EL elements having a lower driving voltage and a longer life than those in Comparative Examples 1 to 3 were obtained. In particular, in Example 2, in addition to lowering the voltage, a lifespan that is more than five times longer than that of Comparative Example 3 was achieved, demonstrating the effects of lowering the voltage and increasing the lifespan achieved by vapor deposition of an acidic material. [Industrial Applicability]

[0093] The organic thin film of the present invention can be used in organic electroluminescence devices, display devices, lighting devices, and the like. [Explanation of symbols]

[0094] 1: Organic EL (electroluminescence) element 2: Substrate 3: Anode 4: Hole injection layer 5: Hole transport layer 6: Light-emitting layer 7:Electron transport layer 8:Electron injection layer 9: Cathode

Claims

1. The organic thin film comprises a 4-benzoic acid-carbazole derivative having a structure represented by the following general formula (1): 【Chemistry 1】 (In general formula (1), R 1 is selected from functional groups including a thiol group, a carboxyl group, a phospho group, a sulfo group, a hydroxyl group, and esters thereof; Ak is a single bond or an alkylene group having 1 to 4 carbon atoms; R 2 , R 3 , R 4 and R 5 are each independently selected from hydrogen, a halogen atom, a cyano group, and a fluorinated alkyl group; R 6 are each independently selected from a halogen element, a fluorinated alkyl group, and a fluorinated aryl group.

2. R in the above general formula (1) 1 is a carboxy group, R 6 The organic thin film of claim 1 , wherein each of is independently selected from fluorine, a fluorinated alkyl group, and a fluorinated aryl group.

3. An organic electroluminescence element having a light-emitting layer between a cathode and an anode, The organic electroluminescence element has a layer between the anode and the light-emitting layer, the layer containing a first material which is a 4-benzoic acid-carbazole derivative having a structure represented by the following general formula (1): 【Chemistry 2】 (In general formula (1), R 1 is selected from functional groups including a thiol group, a carboxyl group, a phospho group, a sulfo group, a hydroxyl group, and esters thereof; Ak is a single bond or an alkylene group having 1 to 4 carbon atoms; R 2 , R 3 , R 4 and R 5 are each independently selected from hydrogen, a halogen atom, a cyano group, and a fluorinated alkyl group; R 6 are each independently selected from a halogen element, a fluorinated alkyl group, and a fluorinated aryl group.

4. The organic electroluminescence device according to claim 3 , further comprising a laminate film of a layer including the first material and a layer including a second material that transports holes, between the anode and the light-emitting layer.

5. a layer including the first material and a second material that transports holes between the anode and the light-emitting layer; The organic electroluminescence device according to claim 3 , further comprising a layer containing the second material between the light emitting layer and the layer containing the first material and the second material.

6. A display device comprising the organic electroluminescence element according to any one of claims 3 to 5.

7. A lighting device comprising the organic electroluminescence element according to any one of claims 3 to 5.